1994
DOI: 10.1177/107769909407100108
|View full text |Cite
|
Sign up to set email alerts
|

Buses and Ballots: The Role of Media Images in a Local Election

Abstract: This study examines the role of media in a local election using media use andpublicperceptionsof mediaand their interactionsas key independent variables. Some support is found for the notion that media do not exert direct ejfects on behavioral outcomes, but rather this process depends on how people perceive the media t h q use in terms of their ties to special interests in the community and the interaction of this perception with media use.Although the role of mass media in national and state elections has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These images refer largely to political news, though not specifiDownloaded by [New York University] at 01:49 02 November 2014 cally to campaigns. Studies have also shown that images of the news media can mediate between media use and a range of outcomes, including attitude change, evaluations, and knowledge of issues (McLeod et al, 1986;Graber, 1988;Fredin & Kosicki, 1989;Kosicki et al, 1994). We see media images as including material about campaigns in general, and presidential campaigns in particular, because campaigns form such a distinct and recurring aspect of news.…”
Section: Media Imagesmentioning
confidence: 91%
“…These images refer largely to political news, though not specifiDownloaded by [New York University] at 01:49 02 November 2014 cally to campaigns. Studies have also shown that images of the news media can mediate between media use and a range of outcomes, including attitude change, evaluations, and knowledge of issues (McLeod et al, 1986;Graber, 1988;Fredin & Kosicki, 1989;Kosicki et al, 1994). We see media images as including material about campaigns in general, and presidential campaigns in particular, because campaigns form such a distinct and recurring aspect of news.…”
Section: Media Imagesmentioning
confidence: 91%
“…Questionnaire items measuring media use, cynicism, involvement, and negativism were generated based on their use in similar surveys measuring the same or related constructs and behaviors (e.g., Austin & Dong, 1995;Austin & Pinkleton, 1995;Craig, Niemi, & Silver, 1990;Kosicki et al, 1994;Kosicki & McLeod, 1990;Luskin, 1990). Items used in indexes, as shown in Table 1, were pretested to improve their measurement of constructs and to ensure accurate respondent understanding.…”
Section: Methodsmentioning
confidence: 99%
“…Although media critics and scholars frequently criticize the media for increasing cynicism and negativism among the electorate, many political communication studies suggest instead that news media use enhances political knowledge, efficacy, and activity. Scholars criticizing the media tend to focus on problematic media content and reporting practices (e.g., Cappella & Jamieson, 1997;Crotty & Jacobson, 1980;Hart, 1994), whereas scholars taking a more optimistic view of the media's role in political decision making have tended to focus on news media use variables (e.g., Chaffee & Schleuder, 1986;Kosicki, Becker, & Fredin, 1994;McLeod & McDonald, 1985;Perloff, 1997;Pinkleton et al, 1998). In these cases, some interesting distinctions have arisen regarding the effects that using various types of media may have on political attitudes.…”
Section: Distinguishing Media Use From Media Perceptionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, to observe accessibility effects, we used each item separately in the data analysis, a common practice in work on media perceptions (e.g., Austin & Pinkleton, 1999;Kosicki et al, 1994).…”
Section: Measurement Of Variablesmentioning
confidence: 99%